2023
DOI: 10.1172/jci.insight.166608
|View full text |Cite
|
Sign up to set email alerts
|

Impaired PPARγ activation by cadmium exacerbates infection-induced lung injury

Abstract: Emerging data indicates an association between environmental heavy metal exposure and lung disease, including lower respiratory tract infections (LRTIs). Here, we show by single cell RNAsequencing an increase in Pparg gene expression in lung macrophages from mice exposed to cadmium and/or infected with S. pneumoniae. However, the heavy metal cadmium or infection mediated an inhibitory post-translational modification of peroxisome proliferator-activated receptor ɣ (PPARɣ) to exacerbate LRTIs. Cadmium and infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Furthermore, another study showed that Cd-metalloprotein is associated with lung adenocarcinoma [ 66 ]. The correlation between Cd levels in male blood and lung functions was confirmed by epidemiological and in vivo, respectively [ 67 , 68 ]. Cd can cause an anti–apoptotic survival response via many signaling pathways, contributing to cell death [ 69 ], repair and survival, or malignant transformation.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, another study showed that Cd-metalloprotein is associated with lung adenocarcinoma [ 66 ]. The correlation between Cd levels in male blood and lung functions was confirmed by epidemiological and in vivo, respectively [ 67 , 68 ]. Cd can cause an anti–apoptotic survival response via many signaling pathways, contributing to cell death [ 69 ], repair and survival, or malignant transformation.…”
Section: Discussionmentioning
confidence: 94%
“…Evidence indicates that ERK and oxidative stress are involved in CdCl 2 -induced inflammation in the lungs of humans and mice [ 4 , 17 , 19 ]. This suggests that these two factors may intensify the exacerbation of asthma induced by CdCl 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The ERK pathway plays a pivotal role in the inflammation induced by CdCl 2 in mouse lung tissue. Exposure to CdCl 2 initiates ERK activation in mouse lung tissue, which subsequently orchestrates the degradation of peroxisome proliferator-activated receptor γ (PPARγ) in macrophages, thereby exacerbating pulmonary infection in mice [ 17 ]. Moreover, CdCl 2 activation of the ERK pathway leads to apoptosis in human bronchial epithelial cells (BEAS-2B) in vitro [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cadmium, a heavy metal toxicant, environmental pollutant and carcinogen, is harmful to immune function and multiple organ systems including cardiovascular, pulmonary, hepatic, renal, skeletal, and reproductive systems [ 6 ]. Cumulative cadmium exposure is a risk factor for the severity of infectious disease including respiratory viral infectious diseases (influenza virus and respiratory syncytial virus), non-airborne viral diseases, bacterial pneumonia, Helicobacter pylori, Toxoplasma gondii, and hepatitis B virus infections [ 7 10 ]. The primary source of cadmium exposure in the general population is through diet and cigarette smoking, with other routes including airborne pollution and occupational exposure [ 11 ].…”
Section: Introductionmentioning
confidence: 99%